Contribution to the study of the beneficial fauna of olive orchards in Porto Martins, Terceira Island, Azores - Moules, Cristina Alexandra Rocha (2022)
The olive tree culture in Terceira Island occupies a strip in Porto Martins area whose fruit is very sought, mainly by tourists and restaurants. The olive tree is very affected by pests, such as the olive fly, which causes high losses and a drastic loss of production. Therefore, large quantities of pesticides are applied whose applications have a great impact, in particular, on beneficial organisms. In this work, the beneficial fauna present in olive groves was identified through the technique of beatings. The impact of the application of pesticides on these beneficial insects present in olive trees with different levels of treatments was also evaluated. For this, orchards with intensive applications, with less intensive applications and one organic orchard were selected to studied and monitoring. It was verified that in the olive groves with intensive and semi-intensive pesticide applications the abundance of beneficial insects was unbalanced, with a low abundance of predatory insects and still high population densities of the olive cottonweed pest. The results obtained point to the fact that chemical treatments do not destroy the target pests and worst contribute to a reduction in auxiliary organisms. In the organic orchard was observed the highest abundance of predatory insects and the lowest abundance of herbivorous insects. These results showed that this type of orchard is in a natural balance and that this is the way to follow in preserving the presence of beneficial insects in the olive parcels because these are very important to keep low pest populations and permit its better control. The conclusions of this study point to the fact that producers can further increase their yield by taking the biological option in their daily practices that will have a lower impact on the beneficial fauna present in the olive groves. At the same time will also permit to preserve the environment and the health of the applicators, producers and of the consumer by obtaining a product without any pesticide residues.